Pelatihan Pembuatan Lansekap Mini untuk Restorasi Atensi - Afifah - Harisah; Ria Wikantari; Abdul Mufti Radja; Mohammad Mochsen Sir; Andi Karina Deapati (Faculty of Engineering UNHAS, 2024)
This Community Service aims to improve Human Resources (HR) skills directly related to the community. The method of implementation is to train partners to create mini landscapes for residential homes from materials found around them, either in the form of objects obtained from nature or other cheap items, so that it is hoped that this can be used as a business to be economically independent in the future, and can restore human attention. From the routine of daily life (ART: Attention Restoration Theory, according to Kaplan), especially after the end of Covid-19. In this community service, lecturers and students provide materials to make a mini landscape, such as rocks, sand, soil, cactus plants, flower pots, and equipment such as scissors and glue. The theme is rocks and cacti. This theme was taken considering that the target whose skills will be added is the younger generation (children and teenagers of the male gender with elementary and middle school education). They are Hafiz Al-Qur'an Ibnu Abbas at Pondok Jabal Hira on Antang Technology Hill, Manggala, Makassar. They are Hafiz Al-Qur'an Ibnu Abbas at Pondok Jabal Hira on Antang Technology Hill, Manggala, Makassar. The results of the service produce mini landscapes, both made individually and in groups, providing valuable educational experiences. Apart from that, the quantitative pre-test and post-test analysis showed an increase in students' understanding; initially, only an average of 25% of students understood the activity material; after the activity was carried out, it rose to 72.22%. This activity also establishes the Islamic Brotherhood.